Fe mediated alleviation effect of cadmium toxicity in mangrove Avicennia marina (Forssk.) Vierh - Li, Jian; Wu, Yueming; Guo, Xiaotong; Jiang, Shan; Leng, Zhanrui; Xia, Jiaojiao; Zhuo, Chongyu; Jia, Hui; Du, Daolin (Frontiers in Marine Science, 2023)
Iron (Fe) supply is one of the key factors in alleviating cadmium (Cd) stress in different plants, including mangroves. However, the effects and mechanisms of Fe in mediating the mangrove response to Cd stress still need to elaborate on the level of plant physiology and metabolism. Herein a 40-day hydroponic study was conducted to evaluate the mediating effect of Fe on Cd tolerance of Avicennia marina (Forssk.) Vierh. Results showed that the Fe supply directly improved the activity of ferric chelate reductase (FCR), increased Fe concentration in tissues, enhanced its competitiveness with Cd, and improved Fe bioavailability, thereby reducing the uptake of Cd by plants. Simultaneously, moderate Fe enhanced the photosynthesis and increased concentrations of total phenolics and tannins in both roots and leaves that play a critical role in chelating and immobilizing Cd, thus restricting the Cd translocation from roots to aboveground tissues. Additionally, the application of Fe significantly upregulated the activity of antioxidant enzymes, including POD and PPO and hence scavenging the reactive oxygen species caused by Cd stress. In conclusion, moderate Fe application improved the growth of A. marina and enhanced its tolerance to Cd at physiological and metabolic levels. Therefore, improving Fe bioavailability will reduce the mangrove degradation caused by Cd contamination, and also this may be a potential way to restore contaminated mangrove ecosystems. Protecting and restoring mangroves is not only essential for preserving biodiversity and supporting coastal ecosystems but also crucial for maintaining their role as crucial carbon sinks (i.e., mangrove blue carbon) combating global warming and climate change.